Efficacy and Safety of Imiquimod 5% as Primary Therapy in Management of Nodular Basal Cell Carcinoma of the Eyelid - Cut Putri Samira; Rossalyn Sandra Andrisa (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To evaluate the efficacy (complete resolution, tolerability, and recurrance of BCC) andsafety (adverse effect during and after treatment) of imiquimod 5% cream as primary therapy inmanagement of nodular basal cell carcinoma.Methods: Journal articles published that were published between 2007 and 2011 related to themanagement of eyelid nodular basal cell carcinoma with imiquimod 5% cream were reviewed.Results: Of all 6 articles: 1 article was randomized trial study; 1 article was case series study; whilethe others were prospective studies. The rate of complete resolution with imiquimod 5% therapy wasoverall high with range 80-100% between all studies. Four studies reported tolerability of imiquimodtherapy assessed by ophthalmologist also range from 80-100%. No occurance of relapse were reportedin all studies. Skin reaction is the most common adverse effect seen with the rate widely variedbetween 53.5% to 100%. Skin reaction could be seen as erythema, crusting, or scabbing in the site ofimiquimod application during and after treatment of the therapy. The other side effects were skinulceration (40-55.5%), keratitis (15%), conjunctivitis (13.3-40%), and ocular discomfort (60%). Nosystemic side effect were reported in all studies.Conclusion: Imiquimod 5% cream gains good evidence of efficacy and safety in treating nodular eyelidand periocular BCC. Imiquimod may be used as first-line treatment in patients with small eyelidnodular BCC located in patients who refuse surgery or have existing pathologies that contraindicatesurgery.Keywords: imiquimod 5% cream, basal cell carcinoma of the eyelid or periocular